A method for preparing a polyurethane-based antimicrobial indwelling catheter
Patent Information
- Application Number
- CN202611299294.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]为了弥补现有技术的不足,解决现有外加抗菌剂共混或涂覆路线中抗菌物质易析出流失、抗菌时效短、存在细胞毒性及诱导耐药风险、涂层与基体结合力差易脱落的问题,和进一步解决现有导管抗菌与抗凝难以兼顾的问题,本发明提出一种基于聚氨酯的抗菌留置导管制备方法
1.本发明抗菌成分不析出、不流失,抗菌持久且使用安全。白藜芦醇以共价键固定在聚氨酯主链上,不存在迁移析出:37℃生理盐水浸泡30d后,实施例1对大肠杆菌的抗菌率仍达98.5%,而物理共混白藜芦醇的对比例2由97.4%降至52.7%,共混纳米银的对比例4降至63.4%,本发明属于非释放型抗菌,不诱导细菌耐药,也无涂层脱落风险,细胞毒性为1级(对比例4纳米银共混样品为3级),实施例1溶血率仅1.3%;
Smart Images

Figure CN122912189A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical polymer materials technology, specifically a method for preparing an antibacterial indwelling catheter based on polyurethane. Background Technology
[0002] Medical indwelling catheters (central venous catheters, dialysis catheters, urinary catheters, etc.) need to be left in the patient's body for a long period of time, and infection and thrombosis are the two most common complications. Clinical statistics show that the incidence of catheter-related bloodstream infection (CRBSI) of dialysis catheters is approximately 0.46 cases per 1000 catheter days (LOCK IT-100 study, Clin J Am Soc Nephrol, 2023), and the incidence of catheter dysfunction due to fibrin sheath reaches 13%-57%. Therefore, the antibacterial and anticoagulant functions of catheters have always been a research focus.
[0003] Existing antibacterial technologies mainly involve blending or coating with external antibacterial agents. For example, CN104984456B discloses an antibacterial polyurethane medical device, its preparation method, and an antibacterial indwelling needle peripheral catheter, which uses polydopamine-loaded silver nanoparticles and is applied through a three-step immersion process, requiring more than 40 hours for the entire coating process; CN101711894B discloses a surface-grafted modified polyurethane medical catheter and its preparation method, which requires first grafting polyvinylpyrrolidone onto the catheter surface with ultraviolet irradiation, and then complexing it with iodine; the Journal of Sun Yat-sen University (Natural Science Edition), Vol. 51, No. 5, 2012, pp. 26-30, also reported a study on grafting povidone-iodine onto the surface of a polyurethane central venous catheter. This approach has several unavoidable problems: First, antibacterial substances such as nano-silver and iodine are release-consuming, continuously precipitating and being lost as the retention time increases, resulting in short antibacterial efficacy; second, the precipitated silver ions and iodine are cytotoxic, and antibiotic-based antibacterial agents also pose a risk of inducing bacterial resistance; third, the coating lacks chemical bonding with the catheter substrate, resulting in poor adhesion and easy detachment under blood flow or catheter friction.
[0004] Regarding anticoagulation, CN115252912A discloses a heparin sodium-modified TPU anticoagulant medical catheter and its preparation method, which involves extruding heparin. However, heparin is highly water-soluble and quickly dissolves and is lost in body fluids, and the catheter lacks antibacterial function. In the covalent grafting route, CN112316218B discloses a zwitterionic polymer-heparin composite coating, its preparation method, and its application. Heparin is grafted via an EDC / NHS coupling system mediated by dopamine deposition, but the heparin grafting amount is only 0.2 μg / cm²-1.68 μg / cm², and the entire aqueous process requires a reaction time of 96 hours at 4°C, which is very long. Similarly, it only provides anticoagulation but not antibacterial properties.
[0005] The closest invention is CN116425946A, which discloses a curcumin-based polyurethane material, its preparation method, and its application, introducing polyphenol chain extenders into the polyurethane backbone. However, this approach relies on the hydrolysis of imine bonds to release curcumin, essentially remaining a slow-release consumable, meaning the antibacterial components will eventually be depleted. Furthermore, its backbone lacks reserved active sites for subsequent surface grafting, requiring surface pretreatment equipment such as plasma or ultraviolet irradiation for anticoagulation modification. Such surface pretreatment processes are complex, have few active sites, and low grafting rates; existing processes typically achieve only about 1.92 μg / cm²-5 μg / cm² of heparin grafting, making it difficult to achieve both antibacterial and anticoagulation effects on the same conduit. Summary of the Invention
[0006] To overcome the shortcomings of existing technologies and address the problems of easy precipitation and loss of antibacterial substances, short antibacterial duration, cytotoxicity and risk of inducing drug resistance, poor adhesion between coating and substrate and easy peeling in existing external antibacterial agent blending or coating routes, and to further solve the problem that existing catheters cannot achieve both antibacterial and anticoagulation, this invention proposes a method for preparing antibacterial indwelling catheters based on polyurethane.
[0007] The technical solution adopted by this invention to solve its technical problem is: a method for preparing an antibacterial indwelling catheter based on polyurethane, comprising the following steps: S1. Raw material dehydration: Dehydrating the polymer polyol; S2, Prepolymerization: Under nitrogen protection, diisocyanate and catalyst are added to the dehydrated polymer polyol to carry out a prepolymerization reaction to obtain an isocyanate-terminated prepolymer. S3, Composite chain extension: Resveratrol dissolved in an organic solvent is mixed with a small molecule diol to form a composite chain extender, which is then added to the isocyanate-terminated prepolymer to carry out a chain extension reaction. The proportion of resveratrol in the composite chain extender is controlled so that the resveratrol residues in the obtained polyurethane segments retain at least one free phenolic hydroxyl group on average, thus obtaining an intrinsic antibacterial polyurethane solution. S4. Post-processing: The intrinsic antibacterial polyurethane solution is vacuum degassed, discharged, granulated and dried to obtain intrinsic antibacterial polyurethane granules. S5. Extrusion molding: The intrinsic antibacterial polyurethane granules are extruded through an extruder and drawn and shaped to obtain an indwelling catheter; S6. Surface functional grafting: First, the indwelling catheter is immersed in an organic solution containing bromopropyne and potassium carbonate to carry out propytization reaction, so that the free phenolic hydroxyl groups of the resveratrol residues are introduced into the alkynyl group; then, the alkynized indwelling catheter is immersed in an aqueous solution containing heparin azide, copper salt catalyst and reducing agent to carry out CuAAC click chemical reaction, so that heparin is covalently grafted on the surface of the indwelling catheter to form a vascular endothelial membrane-like anticoagulant layer; S7. Cleaning and sterilization: Cleaning removes residual copper ions, drying and sterilizing to obtain the polyurethane-based antibacterial indwelling catheter.
[0008] Preferably, the polymer polyol in S1 is polytetrahydrofuran ether diol or polycaprolactone diol, with a number average molecular weight of 1000-2000; the diisocyanate in S2 is hexamethylene diisocyanate or isophorone diisocyanate.
[0009] Preferably, the small molecule diol in S3 is 1,4-butanediol, and the organic solvent is N,N-dimethylformamide; the resveratrol accounts for 10%-60% of the total molar amount of the composite chain extender; the molar ratio of the total hydroxyl groups in the composite chain extender to the isocyanate groups in the isocyanate-terminated prepolymer is 0.95:1-1.05:1.
[0010] Preferably, the catalyst in S2 is dibutyltin dilaurate, and its amount accounts for 0.01%-0.1% of the total mass of the prepolymerization reaction in S2; the molar ratio of the isocyanate group of the diisocyanate to the hydroxyl group of the polymer polyol in S2, n(NCO):n(OH), is 1.8:1-2.2:1; the prepolymerization reaction temperature is 70℃-85℃; and the reaction time is 2h-3h; the chain extension reaction temperature in S3 is 60℃-80℃; and the reaction time is 2h-4h.
[0011] Preferably, the drying temperature in S4 is 80℃-120℃, and the drying is carried out until the moisture content is not higher than 0.02%; the temperature of each zone of the extruder barrel in S5 is 175℃-215℃, and the die temperature is 185℃-200℃.
[0012] Preferably, the solvent of the organic solution in S6 is N,N-dimethylformamide, the temperature of the propargylation reaction is 40℃-60℃, and the time is 6h-12h; the copper salt catalyst is CuSO4, and the reducing agent is sodium ascorbate.
[0013] Preferably, the concentration of CuSO4 in the aqueous solution in S6 is 0.05 mmol / L-2 mmol / L, and the concentration of sodium ascorbate is 2.5 mmol / L-100 mmol / L; the temperature of the CuAAC click chemical reaction is room temperature-40℃, and the time is 1h-6h; during the CuAAC click chemical reaction, the aqueous solution is simultaneously perfused into the lumen of the indwelling catheter.
[0014] Preferably, in step S6, the heparin azidide is replaced with polyvinylpyrrolidone azidide, which is grafted via CuAAC click chemical reaction and then complexed with iodine to form a povidone-iodine antibacterial layer on the surface of the indwelling catheter.
[0015] Preferably, in step S7, residual copper ions are removed by cleaning with EDTA-2Na solution, followed by ultrasonic cleaning with purified water; the sterilization is performed using ethylene oxide.
[0016] Preferably, the heparin grafting amount of the prepared antibacterial indwelling catheter is 8 μg / cm²-12 μg / cm², and the heparin grafting amount is determined by the toluidine blue method.
[0017] The advantages of this invention are: 1. The antibacterial components of this invention do not precipitate or leak, providing long-lasting antibacterial protection and safe use. Resveratrol is covalently fixed to the polyurethane backbone, preventing migration and precipitation. After soaking in physiological saline at 37°C for 30 days, Example 1 still achieved an antibacterial rate of 98.5% against Escherichia coli, while the antibacterial rate of Comparative Example 2 (physical blend of resveratrol) decreased from 97.4% to 52.7%, and that of Comparative Example 4 (blended with nano-silver) decreased to 63.4%. This invention is a non-release antibacterial agent, does not induce bacterial resistance, and has no risk of coating peeling. Its cytotoxicity is grade 1 (comparative Example 4, nano-silver blend sample, is grade 3), and the hemolysis rate of Example 1 is only 1.3%. 2. This invention eliminates the need for surface activation equipment, achieves high grafting site density, large grafting volume, and short process cycle, and integrates antibacterial and anticoagulant functions. The free phenolic hydroxyl groups retained on the chain segment directly serve as grafting sites, eliminating the need for pretreatment equipment such as plasma and ultraviolet irradiation. The heparin grafting volume reaches over 8 μg / cm² (9.6 μg / cm² in Example 1 and 11.2 μg / cm² in Example 3), significantly higher than the approximately 1.92 μg / cm²-5 μg / cm² of existing surface grafting processes and 4.1 μg / cm² of Comparative Example 5. The APTT is extended from 31.5s in the blank catheter to 68.4s, platelet adhesion is reduced from 57 / field of view to 8 / field of view, and the total time of the surface grafting process is shortened from approximately 120h in Comparative Example 5 to approximately 14h. Simulated indwelling for ≥90 days shows no blockage, while Comparative Example 1 shows fibrin sheath encapsulation and blockage after approximately 21 days. 3. Mechanical properties improved rather than decreased. The rigid stilbene structure of resveratrol residues reinforced the polyurethane matrix, increasing the tensile strength from 35.2 MPa in Comparative Example 1 to 42.6 MPa in Example 1 and 47.8 MPa in Example 3, while maintaining an elongation at break of over 423%, fully meeting the requirements for flexibility and strength of indwelling catheters. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a process flow diagram of the preparation method of the present invention; Figure 2 This is a bar chart showing the antibacterial rates of various embodiments and comparative examples of the present invention; Figure 3 This is a line graph showing the antibacterial durability of Example 1, Comparative Examples 2 and 4 of the present invention. Figure 4 The diagram shows the anticoagulant performance (APTT and heparin grafting amount) of various embodiments and comparative examples of the present invention. Figure 5 The bar chart shows the mechanical properties of various embodiments and comparative examples of the present invention. Figure 6 This is a comparison chart of the infrared spectra (FT-IR) of Embodiment 1 and Comparative Example 1 of the present invention; Figure 7 Gel permeation chromatography (GPC) curves of various embodiments of the present invention and Comparative Example 1; Figure 8 The following are differential scanning calorimetry (DSC) curves of Embodiments 1, 3 and Comparative Example 1 of the present invention; Figure 9 This is a comparison of the infrared spectra of heparin azidide and sodium heparin raw materials of the present invention. Figure 10 This is a bar chart showing the effect of CuSO4 concentration on heparin grafting amount in this invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Please refer to Figure 1 A method for preparing an antibacterial indwelling catheter based on polyurethane, the method comprising the following steps: S1. Raw Material Dehydration: The polymer polyol is dehydrated at 100℃-120℃ under a vacuum degree not exceeding -0.09MPa for 1-2 hours until the water content is not higher than 0.05%. The preferred dehydration temperature is 110℃, and the preferred dehydration time is 1.5 hours. The polymer polyol is polytetrahydrofuran ether diol (PTMEG) or polycaprolactone diol (PCL), with a number average molecular weight of 1000-2000. Residual water in the polyol will react with isocyanate to form urea and release bubbles, which consumes raw materials and affects the appearance and performance of the product. Therefore, this step must completely remove the water, reducing the water content to below 0.05% for subsequent reactions to stabilize.
[0022] S2. Prepolymerization: Under nitrogen protection, diisocyanate and a catalyst are added to the dehydrated polymer polyol. The molar ratio of isocyanate groups in the diisocyanate to hydroxyl groups in the polymer polyol, n(NCO):n(OH), is controlled to be 1.8:1-2.2:1, preferably 2:1. The reaction is carried out at 70℃-85℃ for 2-3 hours to obtain an isocyanate-terminated prepolymer. The preferred reaction temperature is 80℃, and the preferred reaction time is 2.5 hours. The diisocyanate is hexamethylene diisocyanate (HDI) or isophorone diisocyanate (IPDI). The catalyst is dibutyltin dilaurate, and its amount accounts for 0.01%-0.1% of the total feed mass, preferably 0.05%. The excessive amount of isocyanate is to ensure that both ends of the prepolymer are end-capped with isocyanate groups, leaving good reaction endpoints for the next chain extension step. Nitrogen protection is to prevent moisture in the air from prematurely consuming the isocyanate groups.
[0023] S3. Composite Chain Extension: Resveratrol is dissolved in N,N-dimethylformamide and mixed with a small molecule diol to form a composite chain extender. This is then added to the isocyanate-terminated prepolymer obtained in S2 for chain extension. Resveratrol accounts for 10%-60% of the total molar amount of the composite chain extender, preferably 25%-40%. The molar ratio of total hydroxyl groups in the composite chain extender to isocyanate groups in the prepolymer is 0.95:1-1.05:1, preferably 1:1. The chain extension reaction temperature is 60℃-80℃, preferably 70℃, and the reaction time is 2h-4h, preferably 3h, to obtain an intrinsic antibacterial polyurethane solution. The small molecule diol is 1,4-butanediol. This step is crucial to the entire process: resveratrol (3,4′,5-trihydroxystilbene) has three phenolic hydroxyl groups. By controlling its proportion within the above range, only 1-2 phenolic hydroxyl groups participate in the chain extension on average during the reaction, ensuring that at least one free phenolic hydroxyl group is retained on average in the resveratrol residues within the chain segment. These retained free phenolic hydroxyl groups serve two purposes: on the one hand, they directly impart intrinsic antibacterial properties to the material without release or loss; on the other hand, they act as ready-made surface grafting active sites, eliminating the need for activation methods such as plasma and ultraviolet irradiation when performing functional grafting later.
[0024] Although resveratrol has three phenolic hydroxyl groups, their activities differ: the 4′ phenolic hydroxyl group is exposed, has minimal steric hindrance, and exhibits the highest activity; the 3′ and 5′ phenolic hydroxyl groups are significantly less active due to steric hindrance from the adjacent benzene ring and intramolecular hydrogen bonding. Under the chain extension conditions of this invention, resveratrol preferentially participates in the aminoesterification reaction with two phenolic hydroxyl groups. In this case, it is equivalent to a difunctional linear chain extender, with the chain extending normally in two directions without forming branching crosslinking points. Branching points can only be formed when all three phenolic hydroxyl groups of the same molecule react, which rarely occurs under the premise of low activity of the 3,5-position hydroxyl group. Based on gelation theory, even under the worst-case scenario (equal activity of all three phenolic hydroxyl groups), when resveratrol accounts for 55% of the total molar amount of the composite chain extender (i.e., the high dosage case in Example 3), the critical gelation conversion rate estimated according to the Flory-Stockmayer theory is approximately 77.9%. However, in the actual reaction, the conversion rate of the 3,5-position hydroxyl group is far below this critical value, and the system remains below the gelation point and does not gel. This conclusion was also confirmed by structural characterization data: the GPC curves of the products in each example all showed a single narrow distribution peak and no high molecular weight shoulder peak. Figure 7 The gel content was less than 0.5% (Table 6), and a clear melting peak appeared on the DSC curves for all of them. Figure 8 This indicates that the product is a linear thermoplastic polyurethane that can be melt-processed, and all embodiments were successfully melt-extruded.
[0025] S4. Post-treatment: The intrinsic antibacterial polyurethane solution obtained in S3 is vacuum degassed, discharged, and granulated, then dried at 80℃-120℃ until the moisture content is no higher than 0.02%; the preferred drying temperature is 100℃. Residual solvent and moisture will form bubbles, cause broken strips or surface defects during extrusion, so it is essential to dry thoroughly after granulation.
[0026] S5. Extrusion molding: The intrinsic antibacterial polyurethane granules obtained in S4 are added to a single screw extruder. The temperature of each zone of the barrel is 175℃-215℃, and the die temperature is 185℃-200℃, preferably 190℃. After extrusion through the die, the material is drawn and shaped to obtain the indwelling catheter.
[0027] S6. Surface Function Grafting: First, alkyneation treatment is performed—the indwelling catheter obtained in S5 is immersed in an N,N-dimethylformamide solution containing bromopropyne and potassium carbonate, and reacted at 40℃-60℃ for 6h-12h, preferably at 50℃ and for 10h. The free phenolic hydroxyl groups on the resveratrol residues undergo alkyneation reaction with bromopropyne, introducing alkyne groups onto the catheter surface. Then, click grafting is performed—the alkyne-treated indwelling catheter is immersed in an aqueous solution containing heparin azide, CuSO4, and sodium ascorbate, wherein the concentration of CuSO4 is 0.05mmol / L-2mmol / L, and the concentration of sodium ascorbate is 2.5mmol / L-100mmol / L. The aqueous solution is simultaneously perfused into the lumen of the indwelling catheter, and reacted at room temperature-40℃ for 1h-6h, preferably at 30℃ and for 4h. Heparin is covalently grafted onto the inner and outer surfaces of the catheter through CuAAC click chemical reaction, forming a vascular endothelial membrane-like anticoagulant layer. Simultaneous perfusion of the inner lumen is to ensure that heparin is also applied to the inner wall of the catheter, since blood flows through the lumen; treating only the outer surface leaves half the potential risks unaddressed. As an alternative, heparin azido can be replaced with polyvinylpyrrolidone azido, which is then grafted and complexed with iodine to form a povidone-iodine antibacterial layer on the catheter surface, suitable for applications requiring higher surface antibacterial properties.
[0028] S7. Cleaning and Sterilization: Clean the catheter with EDTA-2Na solution to remove residual copper ions, then ultrasonically clean with purified water and dry. Finally, sterilize with ethylene oxide to obtain the polyurethane-based antibacterial indwelling catheter. Copper ions are introduced by the click reaction catalyst and must be thoroughly cleaned. EDTA-2Na complexation cleaning is a mature and reliable method.
[0029] The following is combined Figures 2-10 The technical solution of the present invention will be further described in detail through specific embodiments and comparative examples. The raw materials and equipment used in the following embodiments are all commercially available conventional products: polytetrahydrofuran ether glycol (PTMEG, number average molecular weight 2000 or 1000), polycaprolactone glycol (PCL, number average molecular weight 2000), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), dibutyltin dilaurate, resveratrol (3,4′,5-trihydroxystilbene, purity ≥98%), 1,4-butanediol (BDO), N,N-dimethylformamide (DMF), bromopropyne, potassium carbonate, CuSO4, sodium ascorbate, and EDTA-2Na are all conventional chemical reagents; heparin azid is prepared from sodium heparin through conventional azidation modification; the single-screw extruder, vacuum drying oven, fully automatic coagulation analyzer, scanning electron microscope, etc. are all general-purpose equipment.
[0030] Example 1 Includes the following steps: S1. Raw material dehydration: Weigh 100g of PTMEG (Mn=2000) and dehydrate it under vacuum at 110℃ and a vacuum degree not exceeding -0.09MPa for 1.5h. The moisture content was found to be less than 0.05%. S2. Prepolymerization: Under nitrogen protection, add 16.8g of HDI and 0.07g of dibutyltin dilaurate (accounting for 0.05% of the total feed mass), n(NCO):n(OH)=2:1, and react at 80℃ for 2.5h to obtain isocyanate-terminated prepolymer; S3. Composite chain extension: Resveratrol and BDO are weighed according to the following formula: resveratrol accounts for 35% of the total molar amount of composite chain extender and the total hydroxyl group of composite chain extender is 1:1 to the isocyanate group of prepolymer. Resveratrol is first dissolved in DMF, then mixed evenly with BDO and added to the prepolymer. The reaction is carried out at 70℃ for 3 hours to obtain intrinsic antibacterial polyurethane solution. S4. Post-treatment: The above solution is degassed under vacuum, discharged, granulated, and dried at 100℃ to a moisture content of 0.015%. S5. Extrusion molding: A single screw extruder is used. The temperatures of the barrel zones one to four are 185℃, 195℃, 200℃ and 205℃ respectively, and the die temperature is 190℃. After extrusion, the material is drawn and shaped to obtain the indwelling conduit. S6. Surface Function Grafting: First, the catheter is immersed in a DMF solution containing bromopropyne and potassium carbonate and reacted at 50°C for 10 hours to complete the alkyneization; then, the catheter is immersed in an aqueous solution containing 2 mg / mL heparin azide, 1 mmol / L CuSO4, and 25 mmol / L sodium ascorbate, and the solution is simultaneously perfused into the catheter lumen. The reaction is carried out at 30°C for 4 hours, and heparin is grafted through CuAAC click chemical reaction to form a vascular endothelial membrane-like anticoagulant layer; S7. Cleaning and sterilization: Remove residual copper ions by cleaning with EDTA-2Na solution, ultrasonically clean with purified water, dry, and sterilize with ethylene oxide to obtain the antibacterial indwelling catheter.
[0031] Example 2 Includes the following steps: S1. Raw material dehydration: Weigh 100g of PCL (Mn=2000) and dehydrate it under vacuum for 1.5h at 110℃ and a vacuum degree not higher than -0.09MPa; S2. Prepolymerization: Under nitrogen protection, IPDI was added at a ratio of n(NCO):n(OH) = 2:1, and dibutyltin dilaurate was added at 0.05% of the total feed mass. The mixture was reacted at 75°C for 3 hours to obtain an isocyanate-terminated prepolymer. S3, Composite Chain Extender: Resveratrol accounts for 25% of the total molar amount of the composite chain extender, and the total hydroxyl group of the composite chain extender is added to the prepolymer isocyanate group in a 1:1 molar ratio. Resveratrol is dissolved in DMF and mixed with BDO and added to the prepolymer. The reaction is carried out at 65℃ for 3.5h to obtain an intrinsic antibacterial polyurethane solution. S4. Post-processing: Vacuum degassing, discharge, granulation, and drying at 100℃ until the moisture content is no higher than 0.02%; S5. Extrusion molding: The temperature of each zone of the barrel of the single screw extruder is controlled at 180℃-195℃, the die temperature is 188℃, and the extrusion is traction and shaping. S6 and S7 are the same as in Example 1.
[0032] Example 3 Includes the following steps: S1. Raw material dehydration: Weigh 100g of PTMEG (Mn=1000) and dehydrate it under vacuum for 1.5h at 110℃ and a vacuum degree not higher than -0.09MPa; S2, Prepolymerization: Under nitrogen protection, HDI is added at a ratio of n(NCO):n(OH) = 2:1, and dibutyltin dilaurate is added at 0.1% of the total feed mass. The mixture is reacted at 85°C for 2 hours to obtain an isocyanate-terminated prepolymer. S3, Composite chain extension: Resveratrol accounts for 55% of the total molar amount of the composite chain extender, and the total hydroxyl group of the composite chain extender is added to the prepolymer isocyanate group in a 1:1 molar ratio. Resveratrol is dissolved in DMF and mixed with BDO and added to the prepolymer. The reaction is carried out at 80℃ for 2 hours to obtain the intrinsic antibacterial polyurethane solution. S4. Post-processing: Vacuum degassing, discharge, granulation, and drying at 100℃ until the moisture content is no higher than 0.02%; S5. Extrusion molding: The temperature of each zone of the barrel of the single screw extruder is controlled at 195℃-215℃, the die temperature is 198℃, and the extrusion is traction and shaping. S6. Surface functional grafting: Alkylation was reacted at 60°C for 6 hours; the composition of the click grafting aqueous solution was the same as in Example 1 (heparin azidide 2 mg / mL, CuSO4 1 mmol / L, sodium ascorbate 25 mmol / L), and the solution was simultaneously perfused into the lumen and reacted at 40°C for 1 hour. S7 is the same as in Example 1.
[0033] Example 4 This embodiment illustrates the preparation method of heparin azidide and verifies the boundary conditions of the click grafting process, including the following steps: (1) Preparation of heparin azidide: Weigh 1 g of heparin sodium, dissolve it in 50 mL of MES buffer (0.05 mol / L, pH 5.5), add 0.48 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and 0.29 g of N-hydroxysuccinimide (NHS), and activate the carboxyl group on the heparin molecule at room temperature for 30 min; then add 0.31 g of 2-azidoethylamine hydrochloride, and condense the reaction at room temperature for 24 h; transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 3500 Da, dialyze with purified water for 72 h to remove small molecule byproducts and unreacted reagents, and freeze-dry to obtain heparin azidide. Characterization: The FT-IR spectrum shows a characteristic absorption peak of azido group (-N3) at 2108 cm-1 ( Figure 9 This demonstrates the successful introduction of the azido group; elemental analysis revealed an azido substitution degree of 18.6 units per 100 disaccharide units; chromogenic substrate assay showed an anti-Xa factor activity of 152 IU / mg, which, compared to the 178 IU / mg of the raw material heparin sodium, exhibited an anticoagulant activity retention rate of 85.4%; GPC analysis determined its number-average molecular weight to be 1.56 × 10⁻⁶. 4 , compared with the raw material heparin sodium 1.5×10 4 The results were largely consistent, indicating that the mild aqueous phase modification conditions described above did not cause degradation of the heparin skeleton (Table 7).
[0034] (2) Click grafting boundary condition verification: The indwelling catheter was prepared according to steps S1-S5 of Example 1. After propargylation was completed, the catheter was immersed in an aqueous solution containing 2 mg / mL of the above-mentioned heparin azide, 0.05 mmol / L of CuSO4, and 10 mmol / L of sodium ascorbate. The solution was simultaneously perfused into the lumen of the catheter. The reaction was carried out at 40°C for 6 hours, and heparin was grafted by CuAAC click chemical reaction; S7 was the same as in Example 1. The heparin grafting amount was measured to be 8.7 μg / cm², and the APTT was 64.2 s. Comparative Example 1 Except for replacing all the composite chain extenders with BDO (i.e., without adding resveratrol), the catheters were prepared according to the steps of Example 1, and the S6 surface grafting was not performed again, resulting in blank catheters.
[0035] Comparative Example 2 Resveratrol was physically blended with TPU granules at 5% of the polyurethane mass and then extruded without surface grafting.
[0036] Comparative Example 3 Intrinsic antibacterial polyurethane was prepared according to steps S1-S5 of Example 1 and extruded into a conduit, but surface grafting was not performed in S6, that is, it only has antibacterial function and does not have anticoagulation function.
[0037] Comparative Example 4 Nano-silver was blended with TPU granules at 1% of the mass of polyurethane and then extruded.
[0038] Comparative Example 5 Pure TPU catheters were deposited with dopamine on their surface for 24 hours and then placed in MES buffer at pH 5.0-5.5. Heparin was grafted onto the catheters at 4°C for 96 hours using an EDC / NHS coupling system (refer to the technical route of CN112316218B).
[0039] Comparative Example 6 Except for changing the CuSO4 concentration in the grafting aqueous solution to 0.05 mmol / L, the catheter was prepared according to the steps in Example 1. The heparin grafting amount was measured to be 5.8 μg / cm², and the APTT was 51.6 s.
[0040] The present invention employs the following detection method: 1. Antibacterial rate: According to GB / T 31402-2015 "Test method for antibacterial properties of plastic surfaces", the film-applied method was used for determination. The test bacteria were Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 6538). The contact time was 24h. The antibacterial rate was calculated based on the number of recovered colonies.
[0041] 2. Antibacterial durability: The sample was immersed in physiological saline at 37°C and removed after 0, 7, 14 and 30 days of immersion. The antibacterial rate against Escherichia coli was determined by the above-mentioned film application method.
[0042] 3. Mechanical properties: Tensile strength and elongation at break were determined according to GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets".
[0043] 4. Hemolysis rate: The in vitro hemolysis test was conducted in accordance with GB / T 16886.4-2022 "Biological evaluation of medical devices - Part 4: Selection of blood interaction tests" to determine the hemolysis rate.
[0044] 5. Cytotoxicity: Perform cytotoxicity tests using the extract method according to GB / T 16886.5-2017 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity tests" and assign a rating.
[0045] 6. APTT: Take human plasma anticoagulated with sodium citrate, and after the sample is in full contact with the plasma, measure the activated partial thromboplastin time (APTT) using a fully automated coagulation analyzer.
[0046] 7. Platelet adhesion: The sample was contacted with platelet-rich plasma at 37°C for 2 hours. After rinsing, fixing, and gradient dehydration, the number of adhered platelets (platelets / field) was observed and counted under a scanning electron microscope at 3000x magnification.
[0047] 8. Heparin grafting amount: determined by the toluidine blue method—the sample is immersed in toluidine blue solution, and the surface heparin is quantitatively complexed with toluidine blue. After elution, the absorbance is measured by ultraviolet spectrophotometer, and the heparin grafting amount per unit area (μg / cm²) is calculated according to the standard curve.
[0048] 9. Simulated indwelling patency time: Connect the catheter to a 37°C simulated extracorporeal blood circulation device and run it continuously, observing and recording the time when the catheter becomes blocked.
[0049] 10. Infrared Spectroscopy (FT-IR): Measured using a Fourier transform infrared spectrometer with attenuated total reflectance (ATR) method, scanning range 4000 cm⁻¹. -1 -500cm -1 Used to characterize isocyanate groups (2270cm) in polyurethane products. -1 Whether the reaction is complete (nearby area), free phenolic hydroxyl groups (3200cm) -1 -3500cm -1 (broad absorption) and benzene ring skeleton (1600cm) -1 1510cm -1 The presence of ) and the azido group (2108cm) in heparin azidide -1 Characteristic absorption of ).
[0050] 11. Proton nuclear magnetic resonance (¹H-NMR): Using deuterated dimethyl sulfoxide (DMSO-d6) as solvent, the NMR spectrum was measured on a 400MHz NMR spectrometer. The proton signal of the phenolic hydroxyl group was located in the δ8.3-9.2 range, which was used to verify the retention of the free phenolic hydroxyl group on the resveratrol residue.
[0051] 12. Molecular weight and its distribution (GPC): Gel permeation chromatography was used with DMF as the mobile phase and polystyrene as the standard sample for calibration. The number-average molecular weight (Mn) and molecular weight distribution index (PDI) were measured to observe whether there was a single distribution peak.
[0052] 13. Gel content: Weigh a quantitative sample, extract with boiling DMF under reflux for 24 hours, take out the residue, dry it to constant weight and weigh it. The percentage of insoluble matter to sample mass is the gel content, which is used to determine whether cross-linking and gelation have occurred in the system.
[0053] 14. Differential Scanning Calorimetry (DSC): Nitrogen atmosphere, heating rate 10℃ / min, temperature range -80℃ to 200℃, take the second heating curve to read the glass transition temperature (Tg) and melting peak temperature (Tm). The presence of a melting peak indicates that the product is thermoplastic.
[0054] 15. Free phenolic hydroxyl content: determined by the Folin-Ciocalteu method—the quantitative sample is fully swollen and dispersed in DMF and then reacted with the Folin-Ciocalteu reagent. A standard curve is plotted using resveratrol as a standard, and the absorbance at 765 nm is measured. The amount of free phenolic hydroxyl content per unit mass of sample is then calculated (mmol / g).
[0055] 16. Degree of azid substitution: The nitrogen content of heparin azid is determined by elemental analysis, and the degree of azid substitution is calculated based on the number of azid groups per 100 disaccharide units.
[0056] 17. Anti-Xa activity: The anti-Xa activity of the samples (IU / mg) was determined using a chromogenic substrate method anti-Xa activity assay kit according to the kit instructions.
[0057] 18. NCO content in prepolymer: determined by di-n-butylamine titration method—after the prepolymer reacts with excess di-n-butylamine, the remaining di-n-butylamine is titrated with standard hydrochloric acid solution, and the isocyanate group content (%) is calculated. The experimental results obtained by using the above detection methods are shown in the table below: Table 1 Antibacterial rate (%, film application method, refer to GB / T 31402-2015, 24h of action) Table 2 Antibacterial durability (antibacterial rate of Escherichia coli after immersion in physiological saline at 37°C) Table 3 Anticoagulation and Blood Compatibility Table 4 Mechanical Properties (GB / T 1040.3-2006) Table 5 Comparison of Process and Safety Table 6 Structural characterization of intrinsic antimicrobial polyurethane Table 7 Characterization results of heparin azidide Let's look at Tables 1 and 2 first. When they were first made, the antibacterial rates of the samples were actually quite similar; Comparative Example 2, with resveratrol blend, had 97.4%, and Comparative Example 4, with nano-silver blend, even had 99.5%, all looking quite good. However, after soaking for 30 days, the difference became apparent: Comparative Example 2 dropped to 52.7%, Comparative Example 4 dropped to 63.4%, while Example 1 still had 98.5%. The reason is not hard to understand—the blended antibacterial agents are only physically dispersed in the matrix, relying on migration to the surface to exert their effect; they are lost over time. This invention is different; resveratrol is covalently linked to the polyurethane backbone through a chain extension reaction. As long as the molecular chain remains intact, it cannot escape. The free phenolic hydroxyl groups retained on the chain segments continue to exert their antibacterial effect; this is the meaning of "intrinsic antibacterial": no release, no consumption, no loss. Not releasing it has an added benefit: without the antibacterial agent escaping, it won't irritate surrounding tissues, resulting in a cytotoxicity level of only 1, while the nano-silver blend sample reached level 3, with a significantly higher hemolysis rate of 3.9%. This is where the difference in safety for long-term storage lies.
[0058] Let's look at the heparin grafting amount in Table 3. We achieved over 8 μg / cm², with Example 3 reaching 11.2 μg / cm², while Comparative Example 5, using the old route of dopamine plus EDC / NHS, only achieved a grafting amount of 4.1 μg / cm² after soaking at 4°C for 96 hours. The key difference lies in the site density. Resveratrol molecules have three phenolic hydroxyl groups, but only 1-2 are used on average during chain extension, leaving free phenolic hydroxyl groups on each chain segment. These hydroxyl groups are distributed throughout the duct surface, and after alkyneation, each site can be attached to a heparin molecule via click chemistry, resulting in a naturally large number of sites. The CuAAC click reaction itself has high yield and few side reactions, and can be carried out in an aqueous phase at near room temperature. The dopamine route, on the other hand, can only deposit a layer of polydopamine on the surface, relying on the limited amino and phenolic hydroxyl groups for coupling. With fewer sites, the grafting amount is naturally lower, and a low-temperature, long-duration reaction is required. With increased grafting volume, the effects are tangible: APTT increased from 31.5s in the blank catheter to 68.4s, and platelet adhesion decreased from 57 / field of view to 8 / field of view.
[0059] Table 4 shows the mechanical data. Common sense dictates that adding substances to polyurethane can negatively impact its mechanical properties; the tensile strength of Comparative Example 2, after blending with resveratrol, dropped from 35.2 MPa to 31.6 MPa, which is an example. However, in this invention, the tensile strength actually increased to 42.6 MPa, and in Example 3, when resveratrol was added at 55%, it reached 47.8 MPa. The advantage of this approach stems from the rigid stilbene structure of resveratrol—two benzene rings plus an ethylene bridge—which is inherently a rigid unit. Covalently integrating it into the main chain is equivalent to adding reinforcing points within the chain segments, resulting in stronger physical cross-linking of the hard segments and an increase in strength. Of course, more rigid units can make the chain slightly more brittle; the elongation at break in Example 3 decreased to 423%. Therefore, we prefer a resveratrol content of 25%-40%, balancing both strength and toughness.
[0060] Finally, see Table 5. Comparative Example 5 followed the dopamine route, requiring 24 hours of deposition followed by 96 hours of grafting at 4°C, totaling approximately 120 hours, and also necessitating surface pretreatment equipment. This invention, however, involves 10 hours of acetylation followed by 4 hours of click grafting, completing the process in about 14 hours, which can be done using a standard reactor and water bath, making scale-up production straightforward. Comparative Example 3, which only performed antibacterial treatment without grafting, had an APTT of only 32.8 seconds, similar to the control group, indicating that antibacterial treatment alone cannot solve the thrombosis problem. Conversely, Comparative Example 5, which only performed anticoagulation treatment, only achieved an antibacterial rate of 8.7%-9.4%, which is also insufficient. This invention accomplishes both functions with a single catheter, simulating indwelling for ≥90 days without blockage, while Comparative Example 1 was blocked by a fibrin sheath after approximately 21 days. This demonstrates the clinical value of its dual-function integrated design.
[0061] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0062] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing an antibacterial indwelling catheter based on polyurethane, characterized in that, Includes the following steps: S1. Raw material dehydration: Dehydrating the polymer polyol; S2, Prepolymerization: Under nitrogen protection, diisocyanate and catalyst are added to the dehydrated polymer polyol to carry out a prepolymerization reaction to obtain an isocyanate-terminated prepolymer. S3, Composite chain extension: Resveratrol dissolved in an organic solvent is mixed with a small molecule diol to form a composite chain extender, which is then added to the isocyanate-terminated prepolymer to carry out a chain extension reaction. The proportion of resveratrol in the composite chain extender is controlled so that the resveratrol residues in the obtained polyurethane segments retain at least one free phenolic hydroxyl group on average, thus obtaining an intrinsic antibacterial polyurethane solution. S4. Post-processing: The intrinsic antibacterial polyurethane solution is vacuum degassed, discharged, granulated and dried to obtain intrinsic antibacterial polyurethane granules. S5. Extrusion molding: The intrinsic antibacterial polyurethane granules are extruded through an extruder and drawn and shaped to obtain an indwelling catheter; S6. Surface functional grafting: First, the indwelling catheter is immersed in an organic solution containing bromopropyne and potassium carbonate to carry out propytization reaction, so that the free phenolic hydroxyl groups of the resveratrol residues are introduced into the alkynyl group; then, the alkynized indwelling catheter is immersed in an aqueous solution containing heparin azide, copper salt catalyst and reducing agent to carry out CuAAC click chemical reaction, so that heparin is covalently grafted on the surface of the indwelling catheter to form a vascular endothelial membrane-like anticoagulant layer; S7. Cleaning and sterilization: Cleaning removes residual copper ions, drying and sterilizing to obtain the polyurethane-based antibacterial indwelling catheter.
2. The method for preparing an antibacterial indwelling catheter based on polyurethane according to claim 1, characterized in that: The polymer polyol mentioned in S1 is polytetrahydrofuran ether diol or polycaprolactone diol, with a number average molecular weight of 1000-2000; the diisocyanate mentioned in S2 is hexamethylene diisocyanate or isophorone diisocyanate.
3. The method for preparing an antibacterial indwelling catheter based on polyurethane according to claim 1, characterized in that: The small molecule diol in S3 is 1,4-butanediol, and the organic solvent is N,N-dimethylformamide; the resveratrol accounts for 10%-60% of the total molar amount of the composite chain extender; the molar ratio of the total hydroxyl groups in the composite chain extender to the isocyanate groups in the isocyanate-terminated prepolymer is 0.95:1-1.05:
1.
4. The method for preparing a polyurethane-based antibacterial indwelling catheter according to any one of claims 1-3, characterized in that: The catalyst in S2 is dibutyltin dilaurate, and its dosage accounts for 0.01%-0.1% of the total feed mass of the prepolymerization reaction in S2; the molar ratio of the isocyanate group of the diisocyanate to the hydroxyl group of the polymer polyol in S2, n(NCO):n(OH), is 1.8:1-2.2:1; the prepolymerization reaction temperature is 70℃-85℃; and the reaction time is 2h-3h; the chain extension reaction temperature in S3 is 60℃-80℃; and the reaction time is 2h-4h.
5. The method for preparing a polyurethane-based antibacterial indwelling catheter according to any one of claims 1-3, characterized in that: The drying temperature described in S4 is 80℃-120℃, and the drying is carried out until the moisture content is not higher than 0.02%; the temperature of each zone of the extruder barrel in S5 is 175℃-215℃, and the die temperature is 185℃-200℃.
6. The method for preparing an antibacterial indwelling catheter based on polyurethane according to claim 1, characterized in that: The solvent of the organic solution in S6 is N,N-dimethylformamide, the temperature of the propargylation reaction is 40℃-60℃, and the time is 6h-12h; the copper salt catalyst is CuSO4, and the reducing agent is sodium ascorbate.
7. The method for preparing an antibacterial indwelling catheter based on polyurethane according to claim 6, characterized in that: The concentration of CuSO4 in the aqueous solution in S6 is 0.05 mmol / L-2 mmol / L, and the concentration of sodium ascorbate is 10 mmol / L-100 mmol / L; the temperature of the CuAAC click chemical reaction is room temperature-40℃, and the time is 1h-6h; during the CuAAC click chemical reaction, the aqueous solution is simultaneously perfused into the lumen of the indwelling catheter.
8. The method for preparing a polyurethane-based antibacterial indwelling catheter according to any one of claims 1, 6, or 7, characterized in that: In S6, the heparin azidide is replaced with polyvinylpyrrolidone azidide, which is grafted by CuAAC click chemical reaction and then complexed with iodine to form a povidone-iodine antibacterial layer on the surface of the indwelling catheter.
9. The method for preparing an antibacterial indwelling catheter based on polyurethane according to claim 1, characterized in that: In S7, residual copper ions are removed by cleaning with EDTA-2Na solution, followed by ultrasonic cleaning with purified water; the sterilization is performed using ethylene oxide.
10. The method for preparing a polyurethane-based antibacterial indwelling catheter according to claim 1, 6, or 7, characterized in that: The heparin grafting amount of the prepared antibacterial indwelling catheter was 8 μg / cm²-12 μg / cm², and the heparin grafting amount was determined by the toluidine blue method.
Citation Information
Patent Citations
Surface grafting modified polyurethane medical catheter and preparation method thereof
CN101711894B
An antibacterial polyurethane medical device, its preparation method, and an antibacterial indwelling needle peripheral catheter
CN104984456B
A zwitterionic polymer-heparin composite coating, its preparation method, and its application
CN112316218B